ANALISIS TINGKAT PELAYANAN PENDIDIKAN SEKOLAH MENENGAH PERTAMA DI KABUPATEN MALUKU TENGAH - Narto Kaimudin; Rasyid Thaha; Irwan Ade Saputra (ITB Swadharma, 2026)
Providing educational services is an essential component of community empowerment, as it enhances citizens' knowledge and skills. Educational services at the junior high school level aim to develop students' potential to support their social life and development. Although education in Central Maluku Regency has been implemented, the quality of its services remains low. This study aims to examine the factors contributing to the low quality of junior high school educational services in Central Maluku Regency. The research employed a qualitative approach, with the researcher as the main research instrument. The analysis of educational services refers to five service quality dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The findings indicate that the low quality of junior high school educational services is caused by inadequate and uneven distribution of educational facilities and infrastructure, unequal distribution of teachers, low government responsiveness to community needs, lack of guaranteed access to education, and limited government attention to improving educational service quality.Pelayanan pendidikan pada jenjang Sekolah Menengah Pertama (SMP) bertujuan mengembangkan potensi peserta didik agar mampu berperan dalam kehidupan sosial dan pembangunan. Meskipun penyelenggaraan pendidikan di Kabupaten Maluku Tengah telah berjalan, kualitas pelayanannya masih dinilai rendah. Penelitian ini bertujuan untuk mengkaji faktor-faktor penyebab rendahnya pelayanan pendidikan SMP di Kabupaten Maluku Tengah. Penelitian menggunakan pendekatan kualitatif dengan peneliti sebagai instrumen utama. Analisis pelayanan pendidikan mengacu pada lima aspek kualitas pelayanan, yaitu tampilan fisik (tangible), kehandalan (reliability), daya tanggap (responsiveness), keterjaminan (assurance), dan empati (empathy). Hasil penelitian menunjukkan bahwa rendahnya pelayanan pendidikan SMP disebabkan oleh keterbatasan dan ketidakmerataan sarana dan prasarana pendidikan, penyebaran tenaga pendidik yang belum merata, rendahnya daya tanggap pemerintah terhadap kebutuhan masyarakat, belum adanya jaminan akses pendidikan yang optimal, serta kurangnya perhatian pemerintah dalam upaya peningkatan kualitas pelayanan pendidikan